2011
DOI: 10.1007/8904_2011_11
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Arterial Calcification of Infancy: Fatal Clinical Course Associated with a Novel Mutation in ENPP1

Abstract: Generalized arterial calcification of infancy (GACI) is a rare condition characterized by arterial calcification within the internal elastic lamina associated with intimal proliferation, leading to stenosis of great and medium-sized vessels. This disease, caused by mutations in multiple exons of ENPP1, frequently results in death in infancy. Nowadays, the most promising therapeutic compounds for this rare disease are bisphosphonates. We describe a case of GACI associated with the novel mutation c.653A>T (p.D21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 21 publications
(32 reference statements)
0
20
0
Order By: Relevance
“…8 A limited number of case studies have reported on attempts to treat patients with GACI with oral and intravenous bisphosphonates. [21][22][23][24][25] There is no consensus, however, about the efficacy of bisphosphonates on the ectopic mineralization in these disorders. Some studies report apparent improvement, in some cases there has been very little, if any, effect, and in others bisphosphonate treatment has been accompanied by severe side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 A limited number of case studies have reported on attempts to treat patients with GACI with oral and intravenous bisphosphonates. [21][22][23][24][25] There is no consensus, however, about the efficacy of bisphosphonates on the ectopic mineralization in these disorders. Some studies report apparent improvement, in some cases there has been very little, if any, effect, and in others bisphosphonate treatment has been accompanied by severe side effects.…”
Section: Discussionmentioning
confidence: 99%
“…20 Because PPi is relatively unstable in circulation and has a short half-life, administration of bisphosphonates, which are non-hydrolyzable PPi analogs, have been used to treat these patients with ectopic mineralization, including newborns or infants with GACI type 1 with ENPP1 mutations. [21][22][23][24][25] Careful analysis of these studies suggests improvements in some cases, no change in others, and even development of serious side effects in some patients. At the same time, recent demonstration of reduced PPi level in PXE patients suggested that bisphosphonates might be useful to treat ectopic calcification in patients with PXE and GACI type 2 due to ABCC6 mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Bisphosphonates were effective in reducing the progression of the disease in some children with generalized arterial calcification of infancy [60,61,62] but not in others [63]. Severe skeletal toxicity was observed in 1 patient [62].…”
Section: Bisphosphonate Use In Pediatric Patientsmentioning
confidence: 99%
“…It has been reported that treatment with EHDP improved the overall survival of patients with GACI by diminishing arterial calcification (Otero et al, 2013, Edouard et al, 2011, Galletti et al, 2011, Rutsch et al, 2008). Because the dose of EHDP required to inhibit bone resorption is near the one that impairs mineralization, EHDP could also serve as an inhibitor of mineralization in the bone and in the extra bone tissues (Fleisch, 2002).…”
Section: Introductionmentioning
confidence: 99%